Using xCELLigence RTCA Instrument to Measure Cell Adhesion - Hamidi, Hellyeh; Lilja, Johanna; Ivaska, Johanna (Bio-protocol, 2017)
Cell adhesion to neighbouring cells and to the underlying extracellular matrix (ECM) is a fundamental requirement for the existence of multicellular organisms. As such, the formation, stability and dissociation of cell adhesions are subject to tight control in space and time and perturbations within the sophisticated adhesion machinery are associated with a variety of human pathologies. Here, we outline a simple protocol to monitor alterations in cell adhesion to the ECM, for example, following genetic manipulations or overexpression of a protein of interest or in response to drug treatment, using the xCELLigence real-time cell analysis (RTCA) system.